Efforts to Improve Aqidah Akhlak Learning Outcomes Through the Discussion Method for MA Nuriddahlani Probolinggo Students - Devy Habibi Muhammad; Robiatul Adawiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
In the learning process using discussion methods, educators must provide the best activities in the learning process and provide opportunities to students so that students can actively participate in learning that uses discussion methods so that they can exchange opinions so that they can affect learning and effective results. The formulation of this research problem is